2017
DOI: 10.1007/s11284-017-1521-9
|View full text |Cite
|
Sign up to set email alerts
|

Filling the gaps in ecological studies of socioecological systems

Abstract: Our human-dominant world can be viewed as being built up in two parts, social and ecological systems, each consisting of multi-level organizations that interact in a complex manner. However, there are knowledge gaps among those interactions. In this paper, we focus on studies filling two types of gaps in the socioecological system, some of which are case studies in the East Asia region and others are discussed in a more general context. First, we address the gaps between different levels of organizations in ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…One of the characteristics present in social-ecological systems that can be investigated over time involves feedback loops. Human actions in the environment, such as landscape management, can modify functions and processes in the ecological system, which, in turn, can affect human knowledge and behavior (Chen et al 2017). For example, some studies have shown that high pressure on preferred species (for food, medicine, etc.)…”
Section: Culturalmentioning
confidence: 99%
“…One of the characteristics present in social-ecological systems that can be investigated over time involves feedback loops. Human actions in the environment, such as landscape management, can modify functions and processes in the ecological system, which, in turn, can affect human knowledge and behavior (Chen et al 2017). For example, some studies have shown that high pressure on preferred species (for food, medicine, etc.)…”
Section: Culturalmentioning
confidence: 99%
“…Despite the fact that interdisciplinary approaches have used in research for decades [38], the past two decades has seen huge application of SES in explaining the interactions in and between factors in the field of environmental sciences, economics, social sciences as well as medicines and psychology [41] [42]. Scholars on interdisciplinary study of systems provide five levels of interactions that govern the SES [43], interaction levels such as intra-individual, interindividual, organization, community and macropolicy profoundly influence interdependent changes [41]. Changes inside an individual in one level influences changes to neighbouring individual and level, hence the mutual influence and effect at one level impacts diversely and variously at another level [44] [45].…”
Section: Literature Reviewmentioning
confidence: 99%
“…All biodiversity species that can co-exist in human dominated environment are likely to flourish [29], while weak species in human dominated landscape are likely to escape into different habitats. In either case the degree of biodiversity heterogeneity in a particular landscape is pivotal to an efficient and effective functioning of SES [6] [16] [43] [55] [56], in the context of assuring supply and access to ecosystem services. According to [49]…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a dire need to for a drastic shift from reactive data to proactive data (Yang, Wu & Zhu, 2006). Extant literature points to (i) filter right value-embedded information (Iacovidou, et al, 2017) (ii) amplify little-understood, sporadic info-bytes (Kambatla, Kollias, Kumar & Grama, 2014) (iii) provides enabling environment through sustainability presence to connect resources to eco-evo data analytics (Chen, et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%